Azan reader and digital alarm clock / Emirulzaman Supeni and Ahmad Afif Azmi - Supeni, Emirulzaman; Azmi, Ahmad Afif (2005)
Azan reader is implemented using Visual Basic 6.0 Professional Edition .It is because the interface is user-friendly and easy to understand It save the time for azan that had been set and alerts the Muslims users when the time is equal to azan reader. It can play in laptop and desktop computer also The features of azan reader are it have five time solah like zohor,asar ,maghrib,isyak and subuh.lt also has a main time to display the user that what time are going now. This azan reader is suitable for Muslims who are busy in working at office especially doing a job in front of computer. Even though, the market have azan reader software, this azan reader is very easy installing and using. Digital alarm clock is device that show current time and set the time for alarm. The difference on digital alarm clock described here is use one PIC 16F84A as it core this PIC will act as multiplexer and decoder with certain code that will be program in this PIC and control the circuit operation. In this report will describe how the azan reader and digital alarm clock are implemented and work.